Survival Analysis of Tuberculosis Patients Based on Diabetes Mellitus Status in West Sumatra - Basra, Mega Utami; Djafri, Defriman; Fadila, Zurayya (Jurnal Kesehatan Masyarakat, 2024)
Tuberculosis (TB) is still one of the main problems in tropical countries, especially in Indonesia. The existence of conditions that cause decreased immune systems, such as Diabetes Mellitus (DM), can lead to an increased risk of death in people with Tuberculosis. This study aimed to analyze the survival of Tuberculosis patients with a history of DM in West Sumatra Province. This research was conducted from April to October 2022. It is a retrospective cohort study with all TB patients recorded in the TB03 SO data register in West Sumatra Province in 2021 (N=8,299). The samples were all candidates who met the research criteria in the data (n=1,125 TB patients). Data analysis was performed using survival analysis. The results showed that 177 TB patients (15.73%) had a history of DM, and 948 (84.27%) did not. The cumulative probability of survival for TB patients based on non-DM cases on day 150 is 0.95. In contrast, the cumulative probability of survival for patients with a history of DM is lower, namely 0.90. The group of TB patients who suffered from DM, male and more than 45 years old, experienced a more significant decrease in survival.